Techno-Economic Analysis of Off-Grid PV Solar System for Residential Building Load: A Case Study in Baidoa, Somalia - Ahmed , Abdullahi Abdulkadir; Didane, Djamal Hissein; Hussein, Bashir Ali; Al-Alimi, Sami; Manshoor, Bukhari; Saif, Yazid (International Journal of Integrated Engineering, 2024)
The demand for energy is increasing day by day globally. To overcome the problem of energy scarcity, solar energy promises to be one of the best solutions without a significant increase in the carbon footprint of the atmosphere. Currently, most Somalis do not have access to a regular source of power. The country does not have a national grid, relying on outdated, costly and inefficient diesel generators. The energy consumption in Somalia is dependent on firewood and charcoal, dependencies that rely on deforestation and desertification, which negatively influence the agricultural sector and also the environment. In this work, the potential of solar power in Somalia is assessed while estimating the cost of solar panels per household. The aim of this study is to assess the cost, ecological and economic efficiency of the off-grid PV home system in residential buildings in Baidoa, Somalia. A stand-alone solar home system of 1.98kW PV capacity with battery backup is designed by using HOMER software. The daily primary load considered is 7.530 kWh, with a peak of the nominal power of 1.60 kW. The results show that renewable energy sources can replace conventional energy sources and that they would be a viable solution for generating electrical energy in residential houses in Baidoa with a reasonable investment. It was also found that the amount of power produced by solar panels is 7,400kWh/year. With an initial investment of $5580, the annualized life cycle cost of the system is $0.483, the payback period of initial investment is 2 years and 8 months period, and the net present cost (NPC) of the project is $18,684.